PEMANFAATAN LIMBAH KOTORAN KAMBING SEBAGAI TAMBAHAN PUPUK ORGANIK PADA PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE-NURSERY - Saktiyono Sigit Tri Pamungkas; Eky Pamungkas (Universitas Wahid Hasyim, 2019)
This research was conducted to knows the influence goat livestock waste fertilizer application for alternative additional organic fertilizer to palm oil seedling growth on pre-nursery phase. This reasearch was done in green house at Politeknik LPP. The methods was used is non-factorial randomized block design (RBD) with compost (livestock waste fermentation) as primary factor. Dose was used for this reasearch consist of A0 (control), A1 (150 gram), A2 (200 gram), A3 (250 gram), A4 (300 gram). The result of analysis was showing these compost application for additional organic fertilizer to all variable (plant height, number of leaves, gross weight and dry weight) has no different significanly with Duncan Multiple Range Test (DMRT), but on longest roots variable, DMRT test has significantly result at A3 dose (300 gram). The research conclusion is, compost application has influence as additional organik fertilizer for palm oil seddling on pre-nursery phase on longest roots variable with 300 gram dose (A3). Keywords: pre-nursery, compost livestock, palm oil seddling.